Experimental Investigation of the Effect of Downstream Roughness on Flood Wave and Sediment Propagation in case of an Earth-Fill Dam Break by Overtopping - Büyüker, Zehra; Taşkaya, Ebru; Bombar, Gökçen; Tayfur, Gökmen (Fırat University, 2024)
Detection of flood propagation resulting from the failure of the dam is an important topic in terms of detecting and preventing risks that may occur after the dam break in the residential areas at the downstream region. The analysis of flood movement and sediment transport due to flooding is among the factors examined to determine flood movement in earth-fill dams. In this study, the effect of the presence of a residential area at the downstream of the homogeneous earth-fill dam, which was failed by overtopping, on the flood movement was investigated. The dam body was built in a rectangular reinforced concrete channel with a material, which has d50 = 0.441 mm median grain diameter. The width of the dam at the foundation is 106 cm, the width at the crest is 10 cm and the body height is 30 cm. and upstream and downstream slopes of 1:1.6. The dam body is ready by laying three layers of sediment, each layer of which is 10 cm, gradually, compacting each layer with a weight of 1.5 kg, giving the slope and opening a breach on the crest. 13 concrete cubes of 10x10x10 cm were placed to simulate the residential area in the downstream of the dam. The water level at the upstream of dam was gradually increased until the crest level and it was ensured that the water passed from the breach to the downstream of the dam. During the experiments, the distribution of the sediment was recorded with 2 cameras, water levels were measured at 3 different points. Depth profiles of the sediment were obtained with the measurements taken at the end of the experiments. In the case of residential area at the downstream of the dam, the speed of the flood wave hitting the cubes decreases and the time to reach the ruler increases. With the effect of the cubes, the flood wave depths measured downstream of the dam body have increased. Scours and accumulations similar to bridge piers have occurred in the upstream and downstream regions of the cubes. Depending on these accumulations, the sediment height spreading to the settlement area has increased.

Baraj yıkılması sonucu oluşan taşkın hareketinin belirlenmesi, mansap bölgesindeki mevcut yerleşim yerlerinde yıkılma sonrası meydana gelebilecek risklerin saptanması ve önlenmesi açısından önemli bir konudur. Sel nedeniyle suyun yayılması ve sediment taşınımının analiz edilmesi, taşkın hareketinin belirlenmesi için toprak dolgu barajlarda incelenen faktörler arasındadır. Bu çalışmada, üstten aşma ile yıkılan homojen toprak dolgu barajın mansabında yerleşim bölgesi bulunup bulunmamasının taşkın hareketine etkisi araştırılmıştır. Dikdörtgen kesitli betonarme kanalda medyan dane çapı d50=0,441 mm olan malzemeyle baraj gövdesi oluşturulmuştur. Barajın temelde genişliği 106 cm ve krette genişliği 10 cm ve gövde yüksekliği 30 cm'dir ve 1:1,6 memba ve mansap eğimlerine sahiptir. Her biri 10 cm olan üç kat sedimentin kademeli olarak serilmesi, her katın 1,5 kg ağırlık ile sıkıştırılması, eğimin verilmesi ve kret üzerine bir gedik açılması ile baraj gövdesi hazır hale gelmiştir. Baraj mansabına yerleşim alanını simüle etmesi için 10x10x10 cm’lik 13 adet beton küp yerleştirilmiştir. Baraj membasında su seviyesi kret seviyesine kadar kademeli olarak arttırılmış, açılan gedikten suyun baraj mansabına geçmesi sağlanmıştır. Deneyler yapılırken 2 kamera ile sedimentin yayılımı kayıt altına alınmıştır, 3 farklı noktada su derinlikleri ölçülmüştür. Deneyler sonunda yapılan ölçümler ile sedimentin derinlik profilleri elde edilmiştir. Baraj mansabında yerleşim yeri bulunması durumunda, küplere çarpan taşkın dalgasının hızı azalmış ve cetvele ulaşma süresi artmıştır. Küplerin etkisiyle baraj mansabında ölçülen taşkın dalgası derinlikleri artmıştır. Küplerin memba ve mansap bölgelerinde köprü ayağına benzer olarak oyulmalar ve birikmeler meydana gelmiştir. Bu birikmelere bağlı olarak yayılan sediment kalınlığı pürüzlü deneyde artmıştır.
Mansap Pürüzlülüğünün Toprak Dolgu Barajın Üstten Aşma ile Yıkılması Durumunda Taşkın Dalgası ve Sediment Yayılımına Etkisinin Deneysel olarak İncelenmesi
Keywords: Water Resources and Water Structures; Su Kaynakları ve Su Yapıları